MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE PEMBELAJARAN DEMONSTRASI - Pariati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
The purpose of this study is to improve student learning outcomes through the use of demonstration methods and improve the ability of teachers to identify student learning difficulties. This research was conducted at 104214 Elementary School Kedai Durian, this type of research is classroom action research. The implementation of the study was carried out for two cycles consisting of four stages namely planning, action, observation and reflection. The research instrument used was the observation sheet in the form of a check list. Based on the results of observations of research data conducted on efforts to improve the learning outcomes of Indonesian language through demonstration methods in the second grade A Elementary School 104214 Kedai Durian. The results of this study are, several things found in the Pre-action obtained an average value of 51.3 out of 31 students, there were 8 students (25.8%) who had complete learning outcomes and 23 students (74.2 %) the results of the study are not complete. Some of the problems faced by students are students often make noise when given a task to do, students also often disturb their friends or see the work of their friends, students also do not understand the subject matter delivered by the teacher. After giving the action in the first cycle obtained 60.3 student learning outcomes, out of 31 students there were 16 students (51.5%) who completed and 15 students (48.4%) who did not complete. From the results of this study it was concluded that there was an increase in learning outcomes from the pretest to the first cycle, but these learning outcomes have not experienced classical completeness, so the second cycle is still needed to obtain student learning outcomes that are completed classically. After being given action in the second cycle of 31 students there were 23 students completed (74.2%) and 8 students who did not complete (25.8%). With an average value of 74.8. It can be concluded that by the demonstration learning method, it can improve students learning outcomes.